Pengaruh Kualitas Produk, Citra Merek, Dan Persepsi Harga Terhadap Minat Beli Produk Make Over Di Kota Bekasi - Ana Berti Atmajayanti; Dewi Sri Wulandari; Bayu Seno Pitoyo (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to analyze and consider various factors and components that may influence each other between Product Quality, Brand Image and Price Perception on Purchase Interest in Make Over Products in Bekasi City. The sample for this research was 170 respondents who were interested in buying Make Over products in Bekasi City. This type of research uses a quantitative approach. Data was collected directly from respondents using research instruments in the form of questionnaires via Google Form and convenience sampling techniques. then the data results were processed using the SPSS 26 data processing application. The results of this research prove that product quality and brand image have a positive and significant effect on interest in buying Make Over products both partially, but there is no influence of price perception on interest in buying Make Over products either partially. . Simultaneously, product quality, price perception and brand image have a positive and significant effect on purchase intention for Make Over products in Bekasi City.